Enhancing Arabic Speaking Proficiency and Vocabulary Retention Through Baamboozle-Based Game Learning - Faradia Nurya Candra; Ana Taqwa Wati (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Speaking skill and vocabulary mastery are essential for learning Arabic. Low motivation and engagement among students in Arabic language learning process obstacles to language practice, especially in speaking skills. This study evaluated the effectiveness of GBL using bamboozle in eight grades at Al-Fatimah Junior High School Bojonegoro – East Java. This study using a quantitative quasi-experimental design with 56 sample. data were collected through oral and written test and analysed using normality, homogeneity, and independent sample t-test. Results indicated that GBL did not significantly improve speaking skills with a significance value of 0.779 > 0.05. In vocabulary mastery, this method has a substantial impact with a significance value of <0.001 < 0.05. Thus, GBL through Baamboozle is efficacious in improving students' vocabulary mastery but has not significantly improved their speaking skills.